Gallic acid-loaded gel formulation combats skin oxidative stress: development, characterization and ex vivo biological assays - Monteiro e Silva, Silas Arandas; Calixto, Giovana Maria Fioramonti [UNESP]; Cajado, Juliana; de Carvalho, Patrícia Caballieri Antunes; Rodero, Camila Fernanda [UNESP]; Chorilli, Marlus [UNESP]; Leonardi, Gislaine Ricci (MDPI, 2017)
Oxidative stress, which is a result of overproduction and accumulation of free radicals, is the main cause of several skin degenerative diseases, such as aging. Polyphenols, such as gallic acid, are an important class of naturally occurring antioxidants. They have emerged as strong antioxidants that can be used as active cosmetics. The purpose of this study was to develop a gallic acid-loaded cosmetic gel formulation and characterize it using rheological, mechanical, and bioadhesive tests. Its antioxidant effect in the stratum corneum was evaluated by a non-invasive method. According to the characterization tests, the formulation exhibited skin adhesiveness and pseudoplastic behavior without thixotropy, rendering it suitable for use as a cosmetic formulation. Furthermore, the non-invasive method indicated the antioxidant effect in the stratum corneum, with the global lipid peroxide reduction being 33.97 ± 11.66%. Thus, we were able to develop a promising gallic acid-loaded gel formulation that could reduce lipid peroxides and thus combat skin oxidative stress.
Keywords: Antioxidants; Gallic acid; Polymers; Skin administration